Molecular mechanisms of microbial resistance to disinfectants - S. N. Kovalchuk; L. S. Fedorova; E. N. Ilina (Антибиотики и Химиотерапия, 2023)
Dissemination of microbial resistance to biocides, including disinfectants, is one of the acute problem, which poses biological and economic threats to all countries in the world. Understanding the mechanisms of microbial resistance to disinfectants is a necessary scientific basis for searching ways to overcome it. Despite the wide use of disinfectants, developing bacterial resistance to them has been less studied than to antibiotics. This review presents data on the main molecular mechanisms of microbial resistance to disinfectants.